In vitro oxidative metabolism of xenobiotics in the lancet fluke (Dicrocoelium dendriticum) and the effects of albendazole and albendazole sulphoxide ex vivo - Bártíková, Hana; Vokřál, Ivan; Skálová, Lenka; Lamka, Jiří; Szotáková, Barbora (Xenobiotica; the fate of foreign compounds in biological systems, 2010)
Dicrocoeliosis, a parasitic infection caused by Dicrocoelium dendriticum (lancet fluke), is often treated by the anthelmintic drug albendazole (ABZ). In the lancet fluke, ABZ metabolism via enzymatic sulphoxidation was found, but no information about ABZ oxidases has been available. The aim of our project was to find out which enzyme of the lancet fluke is responsible for ABZ sulphoxidation, as well as to assay the activities of oxidation enzymes. We also studied whether ex vivo 24-h exposures of flukes to ABZ or its sulphoxide (ABZ.SO) would alter ABZ sulphoxidation rate and the activities of tested enzymes. In subcellular fractions from flukes, marked activities of peroxidase (Px), glutathione Px (GPx), catalase (CAT), superoxide dismutase, and thioredoxin glutathione reductase were found. Using specific inhibitors, the participation of flavine monooxygenases in ABZ-oxidation was found. The ex vivo exposition of flukes to ABZ or ABZ.SO did not change the rate of ABZ sulphoxidation in vitro, but the ex vivo exposure of flukes to anthelmintics increased Px, CAT, and GPx activity. The modulation of these enzyme activities after ABZ or ABZ.SO exposition may be characteristic of the parasite’s protective mechanism against oxidative stress caused by drug treatment.
Keywords: Sheep; Biotransformation; Glutathione Peroxidase; oxidace-redukce; Albendazole; Xenobiotics; zvířata; glutathionperoxidasa; Subcellular Fractions; Dicrocoelium; albendazol; xenobiotika; inhibitory enzymů; biotransformace; Oxidation-Reduction; Animals; subcelulární frakce; Enzyme Inhibitors; ovce